1996
DOI: 10.1074/jbc.271.35.21142
|View full text |Cite
|
Sign up to set email alerts
|

The β/α Peak Height Ratio of ATP

Abstract: From 31P NMR measurements made in vitro at 38 degrees C, I = 0.25, pH 5. 75-8.5, and calculated free [Mg2+] from 0 to 5 mM, we show that, within the physiological range of cytosolic free [Mg2+] from 0.25 to 1.5 mM, the chemical shift difference between the alpha- and beta-ATP resonances, deltaalphabeta, changes by only 0.6 ppm. Consequently, we developed new formalisms from known acid and Mg2+ dissociation constants by which the observed chemical shift of Pi, deltaPi, and the peak height ratio of the beta- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…Note also that, in determining the free [Mg 2 ] in perfused rat heart ex vivo, the previous authors incorrectly processed the 31 P NMR spectra with 20 Hz line-broadening, while they processed the calibration data with 10 Hz line-broadening (p. 21143). 6 …”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Note also that, in determining the free [Mg 2 ] in perfused rat heart ex vivo, the previous authors incorrectly processed the 31 P NMR spectra with 20 Hz line-broadening, while they processed the calibration data with 10 Hz line-broadening (p. 21143). 6 …”
Section: Resultsmentioning
confidence: 97%
“…The analysis developed by Clarke et al 6 to describe the change in h b/a as a function of free [Mg 2 ] and pH assumed that h b/a is proportional to the concentration of the predominant ATP species in the solution. † Given that the different ATP species have an intermediate rate of exchange (on the NMR time scale), there is no physical basis for this assumption.…”
Section: Theoretical Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…X-ray crystal analysis of Na 2 ATP showed that the adenine base is syn oriented toward the ribose moiety when the crystal contains eight ATP molecules, sixteen sodium ions and twenty-four water molecules in a unit cell (1). It has been reported that the syn and anti orientations are present in equal proportions in the absence of monovalent and divalent cations at neutral pH, but that the adenine base shifted to the anti orientation in the presence of Mg 2ϩ as determined using 1 H, 13 C and 31 P NMR (2)(3)(4)(5)(6). This was most probably because of an ionic interaction between Mg 2ϩ and the ␤-and ␥-phosphates of ATP.…”
mentioning
confidence: 99%